Identification of learning sites: Site selection for validation and prioritization of CSA practices - Bunn, Christian; Lundy, Mark M.; Castro, Fabio (2016)
The presentation laid out a series of suggested learning sites. The goal was to identify partners interested in promoting CSA practices in specific zones. With interested partners, the project would provide access to specific climate change projections, key drivers of change and help identify CSA practices to test, conduct cost-benefit analysis and use to construct site specific resilient strategies.